COVID-19 Vaccine for Elderly: Should We Be Reactive or Proactive? - Siti Setiati; Jessica Marsigit (Acta Medica Indonesiana)
It has been a year since the Indonesian government announced its first COVID-19 identified in Jakarta. Since then, there have been more than 900,000 cases in Indonesia with case fatality rate (CFR) of 2.9%. The number of new cases per day is now ranging from 9,000 cases to almost 13,000 cases. Not only in Indonesia, but the number of new cases along with the mortality rate in other countries, such as Malaysia, Japan, United States, and Europe region also increased dramatically.